JURIDICAL ANALYSIS OF THE RIGHT OF DISASTER VICTIMS TO SUE AGAINST STATE NEGLIGENCE - Dea Ayu Juliasi Dea; Ahmad Sarmadi; Muhamad Zaenudin; Agung Susilo; Faizal Rizal Anugrah (Yasi Learning Education Research, 2026)
The floods and landslides that struck three provinces in Sumatra in December 2025 caused significant material losses, highlighting that the state’s responsibility extends not only to disaster response but also to preventing disasters through responsive policies and consistent law enforcement. This study aims to analyze the legal basis for disaster victims' right to sue the state for negligence in disaster management. Using a normative legal research method, the study examines relevant legislation, legal doctrines, and court decisions. The results indicate that state responsibility is hierarchical and multidimensional, rooted in the welfare state concept. State negligence in disaster management is structural, encompassing epistemic, policy, and accountability failures. The victims' right to sue functions as a corrective legal mechanism supported by strong legal foundations, such as Article 1365 of the Indonesian Civil Code, the Government Administration Law, and the strict liability principle in environmental law. Thus, litigation is not merely a compensatory effort but a strategic instrument to enforce state accountability and environmental justice.